Exploring Musical Affordance of a Virtual Reality Malay Gamelan Through Qualitative Study - Khatriza Ahmad Saffian; Noris Mohd Norowi (Journal of Metaverse, 2025)
Many virtual gamelans are designed to give users alternative access to learn about the gamelan instruments. As the gamelan instruments are physically big and heavy, there is typically limited access to ordinary people who want to learn about the instruments. In recent years, there have been many efforts to virtualize gamelan instruments using various advanced technologies to attract the younger generations and make them accessible. New musical technologies often afford novel interactions that are unattainable with their physical counterparts. This paper investigates the affordance of a virtual reality (VR) gamelan instrument called Air Bonang. Using the qualitative methods under the User-Centered Design (UCD) approach, the affordance of Air Bonang is explored through a ‘breaching experiment’ with the Malay gamelan community. Findings showed that the affordance of the VR gamelan instrument is contextual to three aspects: traditional, exploratory, and collective. The traditional context was based on how Air Bonang was played like the actual bonang, while the exploratory context presents a novel virtual interaction with the instrument. The collective context was afforded through ensemble playing of the instrument. This encompasses how the VR instrument is used in different musical settings regarding its purpose, practicality, relevancy, and reliability.